2007
DOI: 10.1063/1.2794774
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of atmospheric pressure low and radio frequency microjet plasmas produced in a single electrode configuration

Abstract: Microsize jet-type plasmas were generated in a single pin electrode structure source for two separate input frequencies of 50kHz and 13.56MHz in the ambient air. The copper pin electrode radius was 360μm, and it was placed in a Pyrex tube with a radius of 3mm for helium gas supply. Due to the input frequency difference, the generated plasmas showed distinct discharge characteristics for their plasma physical appearances, electrical properties, gas temperatures, and optical properties. Strengths and weaknesses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(46 citation statements)
references
References 15 publications
1
44
0
1
Order By: Relevance
“…1͑a͒, and details of the plasma source can be found in our previous reports. [10][11][12] The powered electrode is a copper pin with a radius of 360 m, and helium gas was introduced axially at a constant flow rate of 3 SLM ͑SLM denotes standard liters per minute͒ through the Pyrex tube. The low frequency power ͑20-80 kHz͒ was used.…”
Section: Methodsmentioning
confidence: 99%
“…1͑a͒, and details of the plasma source can be found in our previous reports. [10][11][12] The powered electrode is a copper pin with a radius of 360 m, and helium gas was introduced axially at a constant flow rate of 3 SLM ͑SLM denotes standard liters per minute͒ through the Pyrex tube. The low frequency power ͑20-80 kHz͒ was used.…”
Section: Methodsmentioning
confidence: 99%
“…Very different is another common jet configuration that often employs a powered electrode wrapped around a hollow dielectric tube through which the feed gas flows axially. [6][7][8][9][10] As the flow field and the electric field are parallel, this type of APGD jets is referred to as the linear-field device. Despite of the scale of their applications, there is considerable ambiguity as to their relative merits for materials processing, thus compromising the value of many application-focused studies.…”
mentioning
confidence: 99%
“…2,[7][8][9][10][11][12][13][14] To determine gas temperature experienced by the material to be treated, a polyamide film was placed at z = 10 mm and the measured spectrum obtained there was used to find its best-fit simulated spectrum to deduce the rotational temperature. Figures 3͑a͒ and 3͑c͒ show that the cross-field and linear-field APGD jets had a rotational temperature of 410 and 520 K respectively at the polyamide surface.…”
mentioning
confidence: 99%
“…A previous study by the authors investigated the corona plasmas driven by two driving frequency ranges, LF and rf, and defined the discharge characteristics at each range. 7 We found that each frequency range induces distinctive discharge features. For instance, rf is favorable for its low breakdown voltage and high plasma density, and the rf field produces a continuous discharge unlike the LF plasma, the discharge of which has a pulselike nature due to space charge accumulation.…”
Section: Introductionmentioning
confidence: 98%